Mononeuritis multiplex: an uncommon neurological manifestation of cytomegalovirus reactivation in an HIV-infected patient - Pedro Palma; Andreia Costa; Raquel Duro; Nélia Neves; Cândida Abreu; António Sarmento (BMC Infectious Diseases, 2018)
Abstract Background Cytomegalovirus (CMV) reactivation with neurological involvement in patients with acquired immunodeficiency syndrome (AIDS) is increasingly rare since the introduction of antiretroviral therapy (ART). Manifestations include encephalitis, myelitis, polyradiculopathy and, less commonly, mononeuritis multiplex (MNM). We report a case of disseminated CMV disease with gastrointestinal and peripheral and central nervous system involvement in a patient with AIDS, manifesting primarily as MNM. Case presentation A 31-year old woman with AIDS presented with a clinical picture of MNM. Electromyography confirmed the clinical findings. CMV DNA was detected in cerebrospinal fluid (CSF) and blood. Gastrointestinal involvement was histologically documented. HIV RNA was also detected in CSF and brain MRI was consistent with HIV encephalopathy. A diagnosis of disseminated CMV disease (with esophagitis, colitis, encephalitis and MNM) and HIV encephalopathy was made. Treatment consisted of ganciclovir and foscarnet, followed by maintenance therapy with valganciclovir. Evolution was favorable and valganciclovir was stopped after sustained immune recovery following ART initiation. Conclusion We discuss the diagnostic approach to CMV neurological disease, with a focus on MNM and CMV encephalitis. Combination therapy with ganciclovir and foscarnet should be considered for all forms of neurological involvement, although available data are scarce. Since there is significant overlap between CMV encephalitis and HIV encephalopathy, ART drugs with higher CSF penetration may have to be considered. ART and immune recovery are essential to improve outcomes.